Treatment of symptomatic knee osteoarthritis with oral salmon calcitonin: results from two phase 3 trials. Issue 4 (April 2015) - Karsdal, M.A.; Byrjalsen, I.; Alexandersen, P.; Bihlet, A.; Andersen, J.R.; Riis, B.J.; Bay-Jensen, A.C.; Christiansen, C.; ,
Summary: Purpose: To evaluate the structure-modifying and symptom efficacy, as well as safety and tolerability of oral salmon calcitonin (sCT) formulated with a 5-CNAC carrier (a molecule based on Eligen ® technology), in osteoarthritis (OA) patients with moderate to severe knee pain and joint structural damage classified as Kellgren and Lawrence (KL)2–3. Methods and design: This is the combined reporting of two randomized, double-blind, multi-center, placebo-controlled trials (CSMC021C2301 and CSMC021C2302), evaluating the efficacy and safety of oral sCT in patients with painful knee OA with structural manifestations, enrolling 1176 and 1030 patients, respectively. Study subjects were randomized (1:1) to oral sCT 0.8 mg twice daily or placebo (PBO) for 24 months. The primary efficacy objectives were to examine the treatment effect compared to placebo on change over 24 months in joint space width (JSW) in the signal knee measured by X-ray, and to examine the change in pain and function using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) questionnaire. Other study parameters included patient and physician global assessment, and biochemical markers of bone (CTX-I) and cartilage degradation (CTX-II). Results: At the 24 month endpoint there was no statistically significant treatment effect on joint space narrowing (JSN) in any of the two studies. In CSMC021C2301 there was a treatment effect on WOMAC (sum of pain, function, stiffness, and total scores) as well as on the biomarkers of bone and joint metabolism, but due to the hierarchical testing procedure the treatment effect was not claimed statistically significant. Conclusions: The present formulation of oral sCT did not provide reproducible clinical benefits in patients with symptomatic knee OA (NCT00486434, NCT00704847 ).